Faktor-Faktor yang Berhubungan dengan Kejadian Kurang Energi Kronis pada Ibu Hamil - Yoan Fransiska; Murdiningsih Murdiningsih; Sri Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Chronic Energy Deficiency is a condition in which the mother is malnourished due to a chronic deficiency of one or more dietary nutrients which results in relatively or absolute health problems for the mother. This study aims to determine knowledge, maternal age, gestational age and income with chronic energy deficiency in pregnant women in the Muara Enim Public Health Center Work Area, Muara Enim Regency in 2021. The method used in this study is an analytical survey with a cross sectional approach. The statistical test used was the Chi-Square test. The population in this study were all multigravida pregnant women, with a sample of 54. Through data analysis with statistical tests using the Chi-Square test, it was found that there was a significant relationship (P-value 0.001), gestational distance (P-value 0.011), and income (P-value = 0.005). with chronic energy deficiency, and there is no relationship between maternal age and chronic energy deficiency in pregnant women with a Pvalue of 0.275. The results of this study can be used as input for the preparation of health programs to reduce the incidence of chronic energy deficiency in pregnant women and as input for improving the quality of health services.